W jaki sposób możemy wyrazić naszą troskę i odpowiedzialność za przyszłość naszej planety i zamieszkującej ją ludzkości? - Rafał Czekalski (Studia Ecologiae et Bioethicae)
This article considers forms of responsibility of people for the future of our planet and future generations. The first point focuses on time preferences, as each generation has different needs and interests and we need to recognize the extent of our responsibility for considering the potential needs and interests of future generations. Undoubtedly, something needs to be done, but can future generations be treated in the same manner as contemporary ones? This is a question that is very difficult to find a satisfactory answer for. Nevertheless, we have found forms in which our responsibility and concern for the future of the planet and humanity is expressed. This article describes the following: advocacy planning, development of ecological education, raising awareness of socio-natural environment problems, and countering climate warming without panic (heuristics of fear). In solving the environmental problems, which condition the future of humanity and the planet, we focus on the concept of Roger Scruton, which is characterized by common sense, distrust of bureaucratic solutions (planning or administrative), and the love of the motherland (oikophilia), which should be the primary motive of any ecological activity. Scruton reminds us of one very important rule: we will not solve environmental problems by going over the heads of the people, for example by introducing regulations (decrees), but through the love of the motherland. This is a typically conservative attitude, distancing itself from the capacity of the state and more international decisions. Problems are resolved here and now, elsewhere they only multiply through the inadequacy of proposed solutions. Such an approach does not eliminate the need for cooperation, which, in the case of the protection of the socio-natural environment, is a necessity.